Using the Lactobacillus gasseri filtrate to protect the mice from the pathogenic bacteria Aeromonas spp. - Mohammed F. Al Marjani; Jehan A. S. Salman; Afraa A. Kadhim; Fahad M. A.; Mohammed J. Muaala (College of Pharmacy / Mustansiriyah University, 2011)
The protective effect of the Probiotic bacteria (Lactobacillus gasseri) against the pathogenic Bacteria (Aeromonas spp) was studied in vivo and in vitro, the inhibitory effect of the Probiotic bacteria filtrate was tested with the Well diffusion method, the filtrate showed a clear inhibiting efficiency toward the pathogenic bacteria and the diameter of the inhibition zone was 16 mm. A group of mice were injected intraperitoneally with (0.25 ml) of the filtrate for 10 days, then they were injected with (0.2 ml) of the Aeromonas spp bacteria living cells ( cell\ml) intraperitoneally, while the control group were injected with 0.25 ml of PBS. The mice were killed after 12 hours of injection with the pathogenic bacteria, they were injected with (5ml) of PBS intraperitoneally, the contents of the periton, Liver and the Spleen were taken after killing the mice, then a dilutions of the Periton contents were made and 0.1 ml was streaking on the media to calculate the number of the growing bacterial colonies, then a part of the Spleen was homogenized and streaking on the media, then the growing colonies were calculated and compared with the control mice, also the macrophage in the contents of the periton were counted, and a samples of the organs were taken directly after the killing and were putted in the formalin solution (10%) for study the histopathological changes. The results shows that the mice who were injected with the probiotic bacteria wasn't effected when they were exposed to the pathogenic bacteria unlike the group that were only exposed to the pathogenic bacteria without being injected with the probiotoic bacteria, and that shows the protective effect of the (Lactobacillus gasseri) against the pathogenic bacteria (Aeromonas spp), and the pathogenic changes shows an inflammatory response and that the tissues were appeared in their natural form.